E-wallet / Siti Nursabrina Bahauddin … [et al.] - Bahauddin, Siti Nursabrina; Parusali, Nurul Izzati; Adam, Khairunnisa; Jamali, Siti Nurdini; Ahmad, Farah Rabbiah (2023)
The modern digital revolution conveyed by ubiquitous internet connectivity and immense usage of mobile phones has created huge possibilities for payment systems to grow. One example is the emergence of sophisticated advanced payment apps such as e-wallets that implemented on cell phones of consumers, provided by the growth of flexible payment providers that try to suggest more incentives to retailers and consumers than banks have done before (Kazan et al, 2018). (Md.Mahmudul Alam, 2021).